Estimating Workability of Steam Boilers Superheaters Considering with the High-Temperature Creep and Uniform Chemical Corrosion - Yefimov, Aleksander; Romashov, Yury; Kavertsev, Valerii (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2019)
It is proposed theoretical estimating workability of steam boilers superheaters on the base of considering the influence of a high-temperature uniform chemical corrosion on of a high-temperature creep of superheater pipes on account of stresses redistributions the pipes walls due to their thickness decreasing. The high-temperature uniform chemical corrosion is presented by the well-known time and temperature dependences of the height of damaged material. The high-temperature creep is considered using the well-known incremental-type theory taking into account the Cachanov-Rabotnov scalar damage parameter. It is proposed the mathematical model of state of superheaters pipes in the form of initial-boundary-value problem in the domain with the moving boundary. The differential equations, initial and boundary conditions of that problem are corresponded to the well-known in the theory of high-temperature creep. Moving of the boundary is corresponded to the well-known time dependence of the height of damaged material due to the high-temperature uniform chemical corrosion. Although, the used theory of creep and the used regularities of uniform corrosion are well-known separately, considering the influence of uniform corrosion on the creep is the complicated problem due to the moving boundary in the corresponded initial-boundary-value problem. It is shown, that the spatial variable replacement allows to reduce the proposed initial-boundary-value problem with the moving boundary to the initial-boundary-value problem with the fixed normed boundary, that allows to simplify numerical solving of the considered problem. The method of lines is discussed for solving the initial-boundary-value problem, representing the mathematical model of the state of pipes of superheaters.